2020
DOI: 10.2147/cmar.s258396
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Novel Epitope Quality-Based Immune Escape Mechanism Reveals Patient’s Suitability for Immune Checkpoint Inhibition</p>

Abstract: Background: Immune checkpoint inhibition, especially the blockade of PD-1 and PD-L1, has become one of the most thriving therapeutic approaches in modern oncology. Immune evasion caused by altered tumor epitope processing (so-called processing escapes) may be one way to explain immune checkpoint inhibition therapy failure. In the present study, we aim to demonstrate the effects of processing escapes on immunotherapy outcome in NSCLC patients. Patients and Methods: Whole exome sequencing data of 400 NSCLC patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…One way of achieving this is altering the presented protein fragment’s size and therefore affinity to bind to the MHC-class I-complex or recognizability to the TCR, which has been identified as a pivotal mechanism in viral infections [ 40 , 41 ]. We have recently shown this mechanism to be active through exonic mutations leading to the altered proteasomal processing of epitopes (“processing escapes”) in lung cancer [ 19 ]. As a result of changes in the chemical composition of the amino acid sequence due to non-synonymous somatic mutations, the proteasomal cleavage properties may change as the different proteasomal subunits show different cleavage preferences for acidic, basic, or hydrophobic amino acids [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One way of achieving this is altering the presented protein fragment’s size and therefore affinity to bind to the MHC-class I-complex or recognizability to the TCR, which has been identified as a pivotal mechanism in viral infections [ 40 , 41 ]. We have recently shown this mechanism to be active through exonic mutations leading to the altered proteasomal processing of epitopes (“processing escapes”) in lung cancer [ 19 ]. As a result of changes in the chemical composition of the amino acid sequence due to non-synonymous somatic mutations, the proteasomal cleavage properties may change as the different proteasomal subunits show different cleavage preferences for acidic, basic, or hydrophobic amino acids [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that alterations in proteasomal antigen processing can be a general mechanism of immune escape in lung cancer [ 19 ]. In the present study, we analyzed if this mechanism is also effective in advanced platinum-treated BC.…”
Section: Introductionmentioning
confidence: 99%
“…These may bring on ineffective neoantigen-specific T cell activation owing to a loss of binding affinity between the neoantigen and the MHC I complex or alteration of the complex's affinity for binding to the TCR. Lung cancer 105 and advanced bladder cancer 106 had a latent immune escape mechanism by altering proteasome antigen processsing. Meanwhile, HLA loss or mutation affected the stability of MHC and production of HLA enhancers, thus, disrupting antigen presentation, which provided an alternative mechanism for immune evasion 103 , 107 , 108 .…”
Section: Neoantigen Vaccines and Immunementioning
confidence: 99%
“…Modern immunotherapeutic approaches have already been investigated in clinical trials in MPM [56][57][58]. One possible explanation for different responses might be in the processing and presentation of tumor-specific epitopes [59,60] important for the activation of tumor-specific T-cells [61]. A complex intracellular pathway is involved in processing these antigenic peptides (Figure S2).…”
Section: Antigen Processing and Presentationmentioning
confidence: 99%